2017
DOI: 10.3945/ajcn.116.151464
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effects of isoflavone formulations against estrogen-deficient bone resorption in peri- and postmenopausal women

Abstract: Age-related estrogen deficiency leads to accelerated bone resorption. There is evidence that, through selective estrogen receptor modulation, isoflavones may exert beneficial effects against estrogen-deficient bone loss. Isoflavone aglycones show higher bioavailability than their glycosidic counterparts and thus may have greater potency. To summarize evidence, we executed a systematic review and meta-analysis examining isoflavone therapies and bone mineral density (BMD) loss in peri- and postmenopausal women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 98 publications
1
46
0
2
Order By: Relevance
“…Phytoestrogen effects on urinary estrogen metabolites have been studied in order to assess their potential protective role against breast cancer. One of the most recent studies reports an increase in the 2:16α-OH-E1 ratio after red clover-derived isoflavone supplementation in postmenopausal osteopenic women [103]. These results are consistent with prior research that found an increase in the 2:16α-OH-E1 ratio after flaxseed supplementation [104,105].…”
Section: Postmenopausal Womensupporting
confidence: 89%
See 1 more Smart Citation
“…Phytoestrogen effects on urinary estrogen metabolites have been studied in order to assess their potential protective role against breast cancer. One of the most recent studies reports an increase in the 2:16α-OH-E1 ratio after red clover-derived isoflavone supplementation in postmenopausal osteopenic women [103]. These results are consistent with prior research that found an increase in the 2:16α-OH-E1 ratio after flaxseed supplementation [104,105].…”
Section: Postmenopausal Womensupporting
confidence: 89%
“…et al demonstrated that red clover-derived isoflavones combined with probiotics attenuated estrogen-deficient bone mineral density loss and improved bone turnover even in postmenopausal women with osteopenia [ 177 ]. Moreover, a recent meta-analysis and systematic review of RCT with perimenopausal and postmenopausal women concluded that isoflavones can be effective in preserving bone mineral density and attenuating accelerated bone resorption [ 103 ]. A possible explanation for these contrasting results could be that estrogens are predominantly antiresorptive agents, so the beneficial effects of phytoestrogens may arise from decreased bone resorption by osteoclasts rather than increased bone formation by osteoblasts.…”
Section: Effect Of Phytoestrogen Intake On Hormones Related To Bonmentioning
confidence: 99%
“…The spine in particular is thought to be the most sensitive to isoflavones because it has a higher content of trabecular bone compared to cortical bone. Trabecular bone has a higher expression of ERβ and a larger surface area for receptor binding [35]. The hip, on the other hand, contains a higher percentage of cortical bone, and is remodeled slower than the spine [36].…”
Section: Effects Of Isoflavones On Menopausal Syndromes and Othersmentioning
confidence: 99%
“…The World Health Organization (WHO) proposes to increase research aimed at examining the potential benefi ts of medicinal plants use in different pharmacological approaches for diseases treatments [12]. There is a growing interest in the study of natural products derived from plants for treatment of bone conditions [13][14][15][16][17]. This is, in part, because they offer the possibility of longer exposure times and fewer secondary complications compared to synthetic drugs [18,19].…”
Section: Introductionmentioning
confidence: 99%